Pallidal Activity in Cervical Dystonia with and Without Head Tremor - Sedov, Alexey (Cerebellum, 2020)
The relationship between two common movement disorders, dystonia and tremor, is controversial. Both deficits have correlates in the network that includes connections between the cerebellum and the basal ganglia. In order to assess the physiological relationship between tremor and dystonia, we measured the activity of 727 pallidal single-neurons during deep brain stimulation surgery in patients with cervical dystonia without head oscillations, cervical dystonia plus jerky oscillations, and cervical dystonia with sinusoidal oscillations. Cluster analyses of spike-train recordings allowed classification of the pallidal activity into burst, pause, and tonic. Burst neurons were more common, and number of spikes within spike and inter-burst intervals was shorter in pure dystonia and jerky oscillation groups compared to the sinusoidal oscillation group. Pause neurons were more common and irregular in pure tremor group compared to pure dystonia and jerky oscillation groups. There was bihemispheric asymmetry in spontaneous firing discharge in pure dystonia and jerky oscillation groups, but not in sinusoidal oscillation group. These results demonstrate that the physiology of pallidal neurons in patients with pure cervical dystonia is similar to those who have cervical dystonia combined with jerky oscillations, but different from those who have cervical dystonia combined with sinusoidal oscillations. These results imply distinct mechanistic underpinnings for different types of head oscillations in cervical dystonia.